A Study Literature Review: Sustainable Finance: Green Finance, Green Investment, And Green Insurance in Indonesia and Global Perspective - Rosydayanti, Evie; Rahayu, Fitria Indrawati; Musfirah, Kharisma Rona; Ahmad, Shandi Maulani; Perkasa, Tito Pramudya Wahyu; Husnan, Lalu Hamdani (Journal of Finance and Business Digital, 2024)
The issue of sustainability is increasingly pressing amidst worsening global economic conditions, including global warming and green land loss. This study aimed to compare the regulation and implementation of sustainable finance in Indonesia with global practices and to understand why the implementation in Indonesia is slower than in other countries and how ESG disclosures can influence this. This study used a literature study that examines various academic sources and reports related to sustainable finance. The finding shows the key challenges that hinder the progress of green finance in Indonesia, such as lack of market awareness, weak regulations, and limited private sector participation compared to significant progress in global practice with strong regulations and high awareness of environmental risks.